Kontribusi Kepemimpinan Transformasional, Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Guru - I.W.C. Adiguna; D.G.H. Divayana; I.G.K.A Sunu (Pascasarjana Universitas Pendidikan Ganesha, 2021)
Teachers have an important role in improving the quality of education, teacher performance is influenced by internal and external factors. This study aims to determine the magnitude of the contribution of transformational leadership, work discipline and work motivation of teachers at the Denpasar Bali Health Vocational School. To achieve this goal researchers used an ex-post facto approach with a sample of 40 people. The collected data were analyzed using simple regression and multiple regression. Based on the research that has been done it is produced that (1) There is a significant contribution of transformational leadership to teacher performance with an effective contribution of 31.27%, (2) There is a significant contribution of work discipline to teacher performance with an effective contribution 24.46%, (3) There is a significant contribution of work motivation to teacher performance with an effective contribution of 29,67%, (4) There is a significant contribution together transformational leadership, work discipline, and work motivation on teacher performance that is equal to 85.40%. Based on the results of this study it can be concluded that transformational leadership, work discipline, and work motivation contribute significantly to teacher performance, thus these three factors can be used as predictors of teacher performance at SMK Kesehatan Bali Dewata Denpasar